Integrate carbon dynamics models for assessing the impact of land use intervention on carbon sequestration ecosystem service. (August 2018) - Liu, Weiguo; Yan, Yan; Wang, Dexiang; Ma, Wu
Highlights: Integrate carbon dynamics in the ecosystem and the atmosphere to account carbon sequestration. Calculate characteristic factor of impact on carbon sequestration to incorporate into LCA. Illustrate the application of the integration by several land use scenarios. Abstract: The land use intervention caused a noticeable impact on carbon sequestration as an ecosystem service. To comprehensively project land use change impact on carbon sequestration, the carbon dynamics models in the ecosystem and the atmosphere were integrated, and characterization factors were calculated for different scenarios. In this study, to illustrate the proposed method, the CENTURY model was used to simulate the carbon dynamics for seven land use change scenarios under two climate change scenarios. Carbon dynamics in the atmosphere was simulated by the Bern2.5CC carbon cycle model. The impact on carbon sequestration was calculated based on the difference of carbon sequestration between the land use change scenario and the corresponding baseline and the decay of CO2 in the atmosphere. According to the simulations, we found that carbon storages and differences of the annual carbon sequestration rate were varied among land use change scenarios and between the two climate change scenarios. After land use conversion, an equilibrium status would be obtained after 100 to 200 years of growth. By integrating the carbon dynamics model with the atmosphere, the characterization factors (CF) were calculated for life cycle assessment. The values of CFs were significantly changed in different land use change scenarios, climate change scenarios and time horizons. The comparison to the previous assessment method indicated that the previous method was too conservative. The results suggested that the method in this study could provide a more reasonable assessment of the impact of land use intervention on carbon sequestration.